Environmental Law Enforcement Through Ecobrick Making Training - Lestari, Berlian Putri Hayu; Dave, Yehezkiel Aldorino Didya; Azizah, Afidatul; Sulistianingsih, Dewi (Jurnal Bina Desa, 2023)
Environmental governance is a new paradigm in the environmental field which is an important part of achieving good governance. Plastics include alkene polymer compounds that have very large molecular shapes. Therefore, it takes 1000 years for plastic to be decomposed by decomposition or decomposition completely. Meanwhile, the production of plastic waste is increasing every day. Society is still difficult apart from the use of plastic. This can have the impact of polluting the environment because of the accumulation of plastic waste. Moreover, the use of plastic in society cannot be controlled. Plastic can also cause the water to become hotter because of its non-porous polymeric nature. In this case, ecobricks are an effective way to deal with plastic waste.. Through Ecobrick, plastic waste is packaged cleanly and dryly and then put into plastic bottles. By reprocessing plastic waste into reusable items such as chairs, tables, trash cans and many other items. With a community service entitled Utilization of Plastic Waste Through Ecobrick Making as an Effort to Reduce Plastic Waste. By empowering the community to manage plastic waste, it becomes something that is useful in the long term. This service activity involved PKK women in Tempuran village, Kaloran sub-district, Temanggung district, Central Java. This activity aims to be able to utilize plastic waste around the village into useful goods. Thus it can create a clean environment and free from plastic waste.